2007
DOI: 10.1002/hed.20505
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patterns of failure and subjective salivary function in patients treated with intensity modulated radiotherapy for head and neck squamous cell carcinoma

Abstract: The predominant pattern of failure in IMRT-treated patients is in the gross tumor volume. Parotid sparing with IMRT resulted in less subjective xerostomia and may improve quality of life in irradiated HNSCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 49 publications
(70 reference statements)
2
44
0
Order By: Relevance
“…The observed low DM incidence rate of 7% (28/399 patients with initial M0-status, (Figure 1) is concordant with that of recent reports in the IMRT literature, ranging between ~ 8-12% (> 90% 3y DM-free survival) [4,6,19,30] following IMRT-chemotherapy, and seems to be lower than many published values following conventional radiation techniques, with ~ 8-25% of DM [1,2,3,8,11,14,24]. A relation between increasing localregional tumor control rates following IMRT and this tendency to decreasing DM rates can not be excluded.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The observed low DM incidence rate of 7% (28/399 patients with initial M0-status, (Figure 1) is concordant with that of recent reports in the IMRT literature, ranging between ~ 8-12% (> 90% 3y DM-free survival) [4,6,19,30] following IMRT-chemotherapy, and seems to be lower than many published values following conventional radiation techniques, with ~ 8-25% of DM [1,2,3,8,11,14,24]. A relation between increasing localregional tumor control rates following IMRT and this tendency to decreasing DM rates can not be excluded.…”
Section: Discussionsupporting
confidence: 89%
“…The site of the primary may influence the rate of DM, with reported ~ 75-80% 2-3y DM-free survival rates in localregionally advanced nasopharyngeal [16,18,21,29], sinonasal [9,13,22], hypopharyngeal [27] and laryngeal tumors [5], ~ 85-95% in oropharyngeal tumors [4,7,15], and ~ 90-95% in oral cavity cancer (OCC) [3][4][5][6]10], respectively. For local-regionally advanced hypopharyngeal tumors, 3y-DM free survival rates of as low as 30% are reported [8,17].…”
Section: Discussionmentioning
confidence: 99%
“…However, IMRT requires very high precision in determining the target volumes in order to avoid marginal misses. There are reports in the literature indicating an increased risk of recurrence in the margins of the irradiated field [51,52,53]. Chen et al [54] reported the need for careful analysis of preoperative imaging studies, operative notes and histopathological reports to determine the appropriate target volumes and postoperative radiotherapy doses.…”
Section: Discussionmentioning
confidence: 99%
“…IMRT results in better dose conformation to the PTV and improved sparing of adjacent uninvolved normal tissues compared with conventional radiotherapy. Numerous studies showed a reduction in the incidence and severity of xerostomia following parotid-sparing IMRT [19][20][21][22][23][24][25][26][27][28][29][30], with post-treatment recovery of saliva production and resultant improvement in patient-reported quality of life [31]. Three randomised controlled trials comparing parotid-sparing IMRT and conventional radiotherapy were reported [12,32,33].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%